Comparative clinicopathological study of biliary intraductal papillary neoplasms and papillary cholangiocarcinomas. Issue 6 (23rd September 2016) - Fujikura, Kohei; Fukumoto, Takumi; Ajiki, Tetsuo; Otani, Kyoko; Kanzawa, Maki; Akita, Masayuki; Kido, Masahiro; Ku, Yonson; Itoh, Tomoo; Zen, Yoh
Abstract : Aims: The aim of this study was to achieve a better definition of intraductal papillary neoplasms of the bile duct (IPNBs). Methods and results: Biliary tumours that showed predominantly intraductal papillary growth were provisionally classified as IPNBs ( n = 25) and papillary cholangiocarcinomas ( n = 27). IPNB was defined as a neoplasm that is confined to the epithelium or is regularly arranged in a high‐papillary architecture along thin fibrovascular stalks, whereas the term 'papillary cholangiocarcinoma' was used for tumours with more complex papillary structures (e.g. irregular papillary branching or mixed with solid–tubular growth). In our consecutive cohort of biliary neoplasms, 5% were classified as IPNBs, and 10% as papillary cholangiocarcinomas. IPNBs differed from papillary cholangiocarcinomas by less advanced invasion, gross mucin overproduction (72% versus 7%), and their prevalent location (84% of IPNBs in intrahepatic/hilar ducts; 70% of papillary cholangiocarcinomas in extrahepatic ducts). Gastric‐type and oncocytic‐type tumours were only detected in IPNBs. Expression of mucin core proteins and cytokeratin 20 significantly differed between the two groups. KRAS and GNAS were wild‐type genotypes in all but one case of KRAS ‐mutated IPNB. Patients with IPNB had better recurrence‐free survival than those with papillary cholangiocarcinoma ( P = 0.007). In multivariate analysis, in which several other prognostic factors (e.g. stromal invasion and lymph node metastasis) were applied, the classification of the two papillary tumours was an independent prognostic factor ( P = 0.040). Conclusions: Given the significant contrast in clinicopathological features between IPNBs and papillary cholangiocarcinomas, it may be more appropriate to use the diagnostic term 'IPNB' for selected tumours that show regular papillary growth, separately from papillary cholangiocarcinomas.